Impact of nutritional status in sarcoidosis patients - Tunç, Şeyma; Yıldız, Pınar; Sungur, Mehmet Ali (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is a systemic granulomatous disease of unknown etiology, with fatigue being one of the most common symptoms. The cause is still under investigation. Factors such as reduced lung function, respiratory muscle weakness, physical deconditioning, corticosteroid-induced myopathy may cause fatigue. Nutritional status of patients is becoming increasingly important in respiratory diseases. This study aimed to investigate the effect of nutritional assessment on peripheral and respiratory muscle strength, as well as exercise capacity in sarcoidosis patients. Methods: This prospective, case-controlled study included 31 sarcoidosis patients not receiving systemic steroid therapy and 24 age- and sex-matched healthy controls. Participants were tested for functional exercise capacity using the 6-minute walk test (6MWT), respiratory muscle strength using maximum inspiratory (MIP) and expiratory pressures (MEP), peripheral muscle strength using handgrip dynamometry and lung function tests. Nutritional status was assessed using the Mini Nutritional Assessment (MNA) questionnaire and body composition analysis by bioelectrical impedance. Results: Despite similar lung function and respiratory muscle strength, sarcoidosis patients showed significantly lower 6MWT distances compared with controls. Sarcoidosis patients had higher body mass index (BMI) and fat mass, while lean mass, smooth muscle mass, skeletal muscle mass, fluid weight and peripheral muscle strength were similar in the patient group and control group. There was no significant difference in MIP, MEP and expected percentage values in sarcoidosis patients compared to the control group. Positive correlations were observed between MIP, MEP and lean body mass, while fat mass was negatively correlated with peak expiratory flow (PEF). Conclusions: This study highlights the need for individualized interventions, including lifestyle modifications, nutrition, and physical rehabilitation, in sarcoidosis-related fatigue. In our study, BMI and fat weight were significantly higher in sarcoidosis patients. In light of this, further research is needed to investigate the impact of adiposity-related inflammation on sarcoidosis progression and outcomes.